2015
DOI: 10.1111/1346-8138.12775
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory features of systemic sclerosis complicated with localized scleroderma

Abstract: Localized scleroderma (LSc) primarily affects skin, whereas systemic sclerosis (SSc) affects skin and various internal organs. LSc and SSc are considered to be basically different diseases, and there is no transition between them. However, LSc and SSc have several common characteristics, including endothelial cell dysfunction, immune activation, and excess fibrosis of the skin, and there exist several SSc cases complicated with LSc during the course of SSc. Clinical and laboratory characteristics of SSc patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 31 publications
0
21
0
2
Order By: Relevance
“…The coexistence of SSc and LoS was already described in 3.2–6.7% of SSc patients [ 14 – 19 ]. Toki et al [ 16 ] found 9 cases (M/F 3/6) of LoS out of 135 SSc patients, and 6 were ANA negative. In the study by Maricq [ 14 ] only 1 case out of 12 developed SSc 6 months after the onset of morphea, while the 2 diseases presented contemporary in other 4 patients; in all these cases the limited SSc subset was described.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of SSc and LoS was already described in 3.2–6.7% of SSc patients [ 14 – 19 ]. Toki et al [ 16 ] found 9 cases (M/F 3/6) of LoS out of 135 SSc patients, and 6 were ANA negative. In the study by Maricq [ 14 ] only 1 case out of 12 developed SSc 6 months after the onset of morphea, while the 2 diseases presented contemporary in other 4 patients; in all these cases the limited SSc subset was described.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, scleroderma, a chronic autoimmune disease, was classified into two categories: systemic scleroderma (also known as systemic sclerosis, SSc) and localized scleroderma (LoS); however, with further study, they are currently considered as two different diseases 1 . In most cases, it is easy to distinguish SSc and LoS from each other just by medical history and clinical manifestations 2 .…”
Section: Localized Sclerodermamentioning
confidence: 99%
“…Scleroderma is a connective tissue disease, and its main features include endothelial cell dysfunction, immune activation and excessive skin fibrosis (86). A previous study demonstrated that patients with scleroderma had a reduced level of exosomes in their serum, which was predominantly due to vascular abnormalities disrupting the transportation of exosomes derived from the fibrocytes of skin tissue (68,87).…”
Section: Exosomes and Other Skin Diseasesmentioning
confidence: 99%